Growth Structural and Spectral Studies on L-Proline Added Ammonium Dihydrogen Phosphate Single Crystals - P. Selvarajan2*, S. Ramalingom3, S. Perumal4, T. Josephine Rani1, Fernando Loretta1 (Recent Research in Science and Technology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Single crystals of pure and L-proline added Ammonium Dihydrogen Phosphate (ADP) were grown from aqueous solutions, employing slow evaporation technique at room temperature. Ã‚Â The grown crystals were subjected to single crystal X- ray diffraction studies and powder X-ray diffraction studies to study their structural characteristics. Fourier transform infrared (FTIR) spectral analysis was performed to identify the presence of various functional groups in the crystals. The UV-Visible-NIR spectral analysis was carried out to confirm the improvement in the transparency of the ADP crystal on the addition of L-proline. The second harmonic generation (SHG) efficiency was investigated to explore the enhancement in the nonlinear optical characteristics of the crystals. The studies performed have revealed the incorporation of L-proline into the lattice ofÃ‚Â ADP crystal.